DATABASE MANAGEMENT PRACTICUM CLASS SCHEDULES IN THE LABORATORY INFORMATION SYSTEM STMIK JAKARTA STI & K WITH VISUAL BASIC 6.0 - Rojoko Rojoko; Ire Puspa Wardhani, SKom, MM (Jurnal Sistem Informasi, 2005)
Use of equipment and laboratory facilities in terms of the practice, requiring the setting time and place, the number of students who are not comparable with the capacity of a room and also the amount of existing equipment. Being one of the obstacles implementing practical activities, on the other side at all times students do not have time to empty it with our lab activities because of the lecture schedule. Because the schedule was made practicum class, where schedules are created by making adjustments to equipment, existing facilities and also for college students. Practicum class schedules are made as well as possible, thereby maximizing use of available equipment and facilities. Use of computers with specialized applications required to accelerate the process of manufacture, let alone a large amount of data processed and the time of urgent needs.